Dulaan a documentary on ethnic theater - Cultural Center of the Philippines; Tiongson, Nicanor G.; Obusan, Ramon A. (Manila The Center, 1992)
Explores Philippine ethnic or folk theater as intertwined with the rituals and life-cycle events of village life, and how contemporary Philippine artists adapt ethnic forms and movements.
VHS.
Narration, Joonee Gamboa ; producers, Rowena E. Concepcion, Mary Ann Ines-Loveria.
With English narration.
Keywords: Folk drama, Philippine; Philippines -- Social life and customs; Documentary